Ovarian tissue cryopreservation for a 3-year-old girl with Mosaic Turner syndrome in China: First case report and literature review - Cheng, Jiaojiao; Ruan, Xiangyan; Du, Juan; Jin, Fengyu; Gu, Muqing; Wu, Yurui; Mueck, Alfred O. (Frontiers in Endocrinology, 2022)
Background: Although it cannot be predicted accurately which young females will develop POI following chemotherapy or irradiation, patients at high risk of POI should be offered ovarian tissue cryopreservation (OTC). Our ovarian tissue cryobank is the first center in China. OTC was firstly performed on a 3-year-old girl with mosaic Turner syndrome (TS) in China. We report this case and present a literature review about TS girls' fertility preservation (FP). Case presentation: Karyotype analysis of umbilical cord blood showed that the girl was diagnosed with TS, 45,X [19]/46,XX [81]. The girl was a 3-year-old girl when her parents would like OTC to preserve fertility. No abnormality was found in the reproductive system, abdominal and cardiac ultrasound, spinal X-ray, and bone age. She was treated with growth hormone (GH) one year ago because of her short stature. GH has been discontinued now. Because of the high risk of POI, OTC was planned. The hormone level before OTC was FSH 4.27 IU/L, LH 0.00 IU/L, E2 < 11.80 pg/ml, AMH 1.06 ng/ml. Pelvic ultrasound showed that the size of the bilateral ovaries was 1.6 cm×0.7-0.8 cm, no enlarged follicles were found, and the maximum diameter of follicles was 0.2-0.37 cm. Ovarian tissue for OTC was taken from the whole right ovary by laparoscopic surgery, and the antral follicles could be seen in ovarian tissue preparation. Sixteen ovarian cortical slices were cryopreserved by slow freezing, with an average of 1380 follicles in round cortical tissue with a diameter of 2 mm, and the follicular density was about 440/mm3. The ovarian tissue from 10 children with non-TS was cryopreserved in our center, the median age was 5 (range 2-8) years old, and the median number of follicles was 766 (range 163-2250) per 2 mm biopsy. The follicles number in this girl were within normal range. Conclusion: TS patients should be evaluated early in childhood to benefit from FP. For highly selected young females with mosaic TS, if the endocrine evaluation does not indicate POI and other health problems do not rule out future pregnancy, it seems reasonable to consider OTC as an FP option.